The Relationship of 25-Hydroxyvitamin D Plasma Levels with Breast Cancer Stadium Assessed from Menopause Status - Ika Waraztuty; Astrid Siska Pratiwi; Melya Susanti; Ira Astuti; Zakirullah (Britain International for Academic Research (BIAR) Publisher, 2021)
Breast cancer is a type of cancer with high incidence and mortality especially in developing countries. Vitamin D regulates the expression a number of genes involved in the development of cancer cells. The aim of this study is to analyze the relationship between 25-hydroxyvitamin D (25 (OH) D) plasma level with breast cancer stage based on menopausal status. This is an observational research method with cross sectional design. Research subjects were 53 newly diagnosed breast cancer patients and had not received chemotherapy. Menopausal status and stage data were obtained from interviews and medical record data. Levels of 25-hydroxyvitamin D plasma were measured (ELISA) method. The results obtained Stage II, III and IV each have an average level of vitamin D of 28,56 ng/ml (95% CI; 23,61 – 33,52 ng/ml), 28,18 ng/ml (95% CI: 24,49 – 31,87 ng/ml) and 27,86 ng/ml (95% CI: 22,68 – 33,04 ng/ml).The average plasma concentration of 25 (OH) D in pre-menopausal patients is 28,54 ng/ml and average plasma 25 (OH) D levels in post-menopausal patients is 27,79 ng/ml. There was no significant relationship between plasma levels of 25 (OH) D and breast cancer stage in both pre-menopausal and post-menopausal patients.